2012
DOI: 10.1007/s10646-012-0880-9
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of atrazine on embryo-larval development of Rhinella arenarum (Anura: Bufonidae)

Abstract: Atrazine (ATR), one of the most widely used herbicides in the world, affects not only target organisms but also the biota in general. Here, the teratogenic and neurotoxic effects of ATR on Rhinella arenarum (South American toad) embryos, and larvae were evaluated by means of standardized bioassays during acute and chronic exposures. The herbicide had a significant incidence of malformations, with a Teratogenic Index (TI) of 3.28. The main effects were delayed development, reduced body size, microcephaly, axial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 38 publications
2
18
0
7
Order By: Relevance
“…It is likely that pesticide exposed tadpoles are at a disadvantage under natural conditions and may face threats and indirect mortality as a consequence of delayed development. Delayed development and metamorphosis due to exposure to other pesticides have also been reported earlier for D. melanostiscus (Jayawardena et al 2011;Wijesinghe et al 2011) and other amphibian species (Svartz et al 2012;Saka et al 2013). Among other factors, increased energetic costs involved in abnormal behaviour could have led to prolong developmental period of these tadpoles.…”
Section: Discussionsupporting
confidence: 62%
“…It is likely that pesticide exposed tadpoles are at a disadvantage under natural conditions and may face threats and indirect mortality as a consequence of delayed development. Delayed development and metamorphosis due to exposure to other pesticides have also been reported earlier for D. melanostiscus (Jayawardena et al 2011;Wijesinghe et al 2011) and other amphibian species (Svartz et al 2012;Saka et al 2013). Among other factors, increased energetic costs involved in abnormal behaviour could have led to prolong developmental period of these tadpoles.…”
Section: Discussionsupporting
confidence: 62%
“…The influence of salicylic acid on FCF was also significant (p < 0.05) in all salicylic acid exposed groups. It is well known that early life stages of fish are generally regarded as the most sensitive to toxic agents (Hutchington et al, 1998;Wiegand et al, 2001;Hostovsky et al, 2012;Svartz et al, 2012). Zivna et al (2013) found increased body weight in groups exposed to 120 and 250 mg/l of acetylsalicylic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Early life stages of fish are generally regarded as the most sensitive to toxic agents (Hutchington et al, 1998;Wiegand et al, 2001;Hostovsky et al, 2012;Svartz et al, 2012) and are ideal models for determining responses to environmental contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…ATZ is one of the important environmental pollutants, especially for surface waters (De Geronimo et al, 2014), but the solubility of ATZ is low and it did not cause high mortality on aquatic organisms (Lenkowski et al, 2010;Svartz et al, 2012;Chromcova et al, 2013). So, the LC 50 of ATZ could not be obtained up to 200 mg/L exposure in embryos or tadpoles of X. laevis.…”
Section: Discussionmentioning
confidence: 99%